Spaces of Feeling : Affect and Awareness in Modernist Literature - Figlerowicz, Marta (Book collections on Project MUSE., 2017)
"Can other people notice our affects more easily than we do? In Spaces of Feeling, Marta Figlerowicz examines modernist novels and poems that treat this possibility as electrifying, but also deeply disturbing. Their characters and lyric speakers are undone, Figlerowicz posits, by the realization that they depend on others to solve their inward affective conundrums--and that, to these other people, their feelings often do not seem mysterious at all. Spaces of Feeling features close readings of works by Virginia Woolf, James Baldwin, John Ashbery, Ralph Ellison, Marcel Proust, F. Scott Fitzgerald, Sylvia Plath, and Wallace Stevens. Figlerowicz points out that these poets and novelists often place their protagonists in domestic spaces--such as bedrooms, living rooms, and basements--in which their cognitive dependence on other characters inhabiting these spaces becomes clear. Figlerowicz highlights the diversity of aesthetic and sociopolitical contexts in which these affective dependencies become central to these authors' representations of selfhood. By setting these novels and poems in conversation with the work of contemporary theorists, she illuminates pressing and unanswered questions about subjectivity"--